Role of Formyl Peptide Receptors in Gastrointestinal Healing - Prevete, N.; de Paulis, A.; Sgambato, D.; Melillo, R.M.; D'Argenio, G.; Romano, L.; Zagari, R.M.; Romano, M. (Current Pharmaceutical Design, 2018)
The wound healing and the barrier restoration of the gastrointestinal (GI) mucosa must be continuously ensured to allow homeostasis of the gastrointestinal tract and of all the surrounding tissues. Several lines of the evidence report a key role of innate immunity, and in particular of Pattern Recognition Receptors (PRRs), in controlling the homeostasis of GI tract by sensing commensal and pathogen bacteria, activating the immune response and regulating epithelial repair, thus guaranteeing the morphological and functional recovery of the injured tissue. We will discuss the role of a particular class of PRRs - the Formyl Peptide Receptors - in the homeostasis of GI mucosa. We here report the results of studies that strongly suggest the possibility that the activation of FPRs is crucial in the maintenance of homeostasis of the GI tract and provide indications of the potential clinical relevance of new treatment regimens involving FPR modulation for several GI disorders.
Keywords: epithelial repair